(untitled) (Research, Society and Development, 2020)
Objective: To analyze the factors that influence the quality of life (QOL) and the level of hopelessness of family members of chemical dependents (DQ). Method: 104 relatives of dependents undergoing treatment participated. A sociodemographic profile form, the Brazilian Economic Classification Criterion (CCEB), the Beck Hopelessness Scale (BHS), and the World Health Organization Quality of Life (WHOQOL-bref) were used. Results: there was a predominance of a moderate level of hopelessness and impaired QOL, especially in the environment domain. Being single, having a lower monthly income, having a family member who uses drugs for more than five years, not being in the job market, having three or fewer people living in residence, not having their transport and being the user’s parent negatively influence the QOL. Illiterate and low-income family members had more hopelessness. Conclusion: sociodemographic characteristics influence QOL and the level of hopelessness and it is important to implement policies that improve this data to obtain better QoL and hopelessness rates.